Infected dentigerous cyst due to traumatic injury in impacted of mandible canine: a case report - Muhajir, Idawati; Adiantoro, Seto; Hardianto, Andri; Rizki, Kiki A. (Journal of Case Reports in Dental Medicine, 2019)
Objective: This case study is a case of infected dentigerous cyst involving all erupted incisor teeth and impacted mandible canine. Diagnosis of results from clinical examination, radiographic and histopathologic.Methods: The initial treatment was antibiotic therapy for 2 week, followed with cyst enucleation, extracted of the all fourth incisors and odontectomy lower left canine, lower premolar and upper right molar through intraoral approach under general anesthesiaResults: The evaluation of 2 weeks post surgery treatment showed the healing was good and the chin region showed no sign of inflammation, the color of the tissue was similar to its surrounding.Conclusion: Last sentence of abstract should be a conclusion or further treatment plan for the case. Histological examination and medical history should be placed before the treatment procedureKeywords: Dentigerous Cyst, Enucleation, Infection.